Neonatal Head Ultrasound: A Review and Update—Part 2. Issue 3 (September 2019) - Maller, Vijetha Vinod; Choudhri, Asim Fiaz; Cohen, Harris L.
Abstract : Abstract: Neonatal head ultrasound has a key role in triaging neonates with antenatal imaging or postnatal clinical concerns. This article will discuss key features of various intracranial pathologies of concern in term infants. It will also illustrate various congenital malformations.